Prophetic Education at Pesantren As A Efforts To Prevent Religious Radicalism - Dimas Indianto s; Sunhaji; Intan Nur Azizah; Ahmad Roja Badrus Zaman (IJORER : International Journal of Recent Educational Research, 2021)
Whether it is recognized or not, religion is the most influencing factor in many social conflict phenomena. An unbalanced understanding of religion is suspected of being one of the triggers. Thus, efforts are needed to educate the public about good religious behaviour so that people understand that religion's existence is to create harmony in life, not contrary to incite hostility. Pesantren is one of the alternatives which is expected to be a way out to untangle the tangled threads of religious issues that have become a classic problem in Indonesia today. Pesantren have an essential role in realizing peace in heterogeneous life, namely through prophetic education. One of the pesantren that applies a predictive education pattern is Pesantren An Najah Purwokerto. This research is qualitative, to analyze prophetic teaching at Pesantren An Najah Purwokerto to prevent religious radicalism and describe the supporting and inhibiting factors of prophetic education at Pesantren An Najah Purwokerto. The results showed that the application of prophetic teaching at Pesantren An Najah Purwokerto through several activities, including (1) Introducing the concept of "liyan" or the other in the context of social or community life; (2) Grounding the rationales of the "hubbul wathan" nationalism; (3) Implementing "Peace Education". (4) Religious education based on local culture.